Efforts To Improve Learning Outcomes Of Upper Passing By Applying Audio Visual Media In Volleyball Learning For Class Vi Mis 05 Darussalam Kepahiang - Ego Anggara; Martiani Martiani; Ajis Sumantri (Universitas Dehasen Bengkulu, 2026)
This study aims to improve the learning outcomes of the basic technique of overhand passing in volleyball through the application of audio-visual media for students in Class VI MIS 05 Darussalam Kepahiang. The main issues identified in the learning process are the low understanding and skills of students in executing overhand passes, as well as learning outcomes that have not yet reached the minimum completeness criteria (KKM). The research method used is Classroom Action Research (CAR), which consists of two cycles, each encompassing stages of planning, implementation, observation, and reflection. Data were collected through observations and pre-test and post-test assessments in each cycle. The results showed a significant improvement in students' overhand passing abilities. In Cycle I, the average post-test score increased to 58.33 from a pre-test score of 42.33, but no students met the KKM. After improvements were made in Cycle II, the average post-test score rose to 82.66, with 26 out of 30 students achieving completeness. The percentage increase in learning outcomes reached 81%, demonstrating the effectiveness of using audio-visual media in supporting the understanding of the overhand passing technique in volleyball. Additionally, observation results showed an improvement in assessment criteria from the